Pengaruh Harga Karet, Minyak Kelapa Sawit, Dan Batu Bara Terhadap Jumlah Penduduk Miskin Di Sumatera Selatan - Ayu Geby Gisela Syaputri; Muhammad Bahrul Ulum (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
The purpose of this study was to determine the effect of rubber, palm oil and coal prices on poverty in SouthSumatra. The research period starts from 2010 to 2021. This study uses a multiple regression analysis tool. In this studyit was concluded that the price of rubber and palm oil had a positive and not significant effect on the number of poorpeople in South Sumatra. The price of coal has a negative and insignificant effect on the number of poor people inSouth Sumatra. Taken together, the prices of rubber, palm oil and coal have no significant effect on the number of poorpeople in South Sumatra.